STILISTIKA AL-QUR’AN; (Ragam Gaya Bahasa Ayat-ayat Ṭalab dalam Diskursus Stilistika) - Wahyu Hanafi (Institut Agama Islam Ngawi, 2017)
The Qur’an has its own miracle that no holy books before had, it has beautifull language and great literature. The one of it’s beauty comes from the structure of al-Amr and al-Nahy inside it. Stylistics is a excellent method that is able to discover the structure of the language style of al-Amr and al-Nahy in the Qur’an. So that expanding the term of stylistics Qur’an. Stylistics analysis of the Qur’an at this stage is focused on the syntactic domains, namely an analysis of the pattern formation of said structure, the sentence structure, sentence structure relationship, as well as the influence of the word’s that have implications to the meaning. Finally, it’s able to find the meaning of dialogue in the structure.